Right Atrial Myocardial Remodeling in Children With Atrial Septal Defect Involves Inflammation, Growth, Fibrosis, and Apoptosis - Rouatbi, Hatem; Farhat, Nesrine; Heying, Ruth; Gérard, Arlette; Vazquez-Jimenez, Jaime F.; Seghaye, Marie-Christine (Frontiers in Pediatrics, 2020)
Introduction Myocardial remodelling due to large atrial septum defect (ASD) is macroscopically characterized by dilation of the right-sided cardiac cavities secondary to volume overload, the cellular mechanisms of which are not yet understood. We postulated that inflammation, fibrosis and cell death are actors of right atrial remodelling secondary to ASD. Patients and Methods In 12 children with large ASD (median age: 63 months ), expression of genes coding for proteins involved in the response to cell stress and -protection, inflammation, growth and angiogenesis, fibrosis, and apoptosis was assessed by RT-PCR in right atrial myocardial biopsies taken during cardiac surgery. The presence of cytokines in myocardial cells was confirmed by immunohistochemistry and effective apoptosis by TUNEL assay. Results In all patients investigated, a cellular response to early mechanical stress with the initiation of early protective mechanisms, of inflammation (and its control), -growth, and -angiogenesis, of fibrosis and apoptosis was present. The apoptotic index assessed by TUNEL assay averaged 0,3%. Conclusions In children with large ASD, macroscopic right atrial remodelling relates to cellular mechanisms involving the expression of numerous genes that either still act to protect cells and tissues but that also harm as they initiate and/or sustain inflammation, fibrosis and cell death by apoptosis. This may contribute to long term morbidity in patients with ASD.